Lipase and esterase: to what extent can this classification be applied accurately? - Lopes, Danielle Branta; Fraga, Laira Priscila; Fleuri, Luciana Francisco [UNESP]; Macedo, Gabriela Alves (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2011)
Tecnologia enzimática é um campo de conhecimento cada vez maior, e, nos últimos anos, esta tecnologia tem apresentado um interesse crescente, devido à busca de novos paradigmas em diversos processos produtivos. Lipases, esterases e cutinases são as enzimas usadas em uma ampla gama de processos que envolvem reações de síntese e hidrólise. O objetivo deste trabalho foi investigar e comparar as atividades de lipase e esterase de quatro enzimas já classificadas como lipases e uma como cutinase, na presença de substratos naturais e sintéticos. Todas as enzimas testadas apresentaram atividades específicas tanto de esterase como de lipase. A maior atividade específica de esterase foi observada para a lipase de Aspergillus 1068 em substrato natural e a cutinase de F. oxysporum em substrato sintético, enquanto a atividade específica de lipase mais alta foi observada para a lipase de Geotrichum sp. em substrato natural e a cutinase de F. oxysporum em substrato sintético. Estes resultados permitem visualizar algumas interfaces independentes de atividade lipolítica para todas as lipases testadas. de acordo com estes estudos, uma nova e mais ampla definição de lipase pode ser necessária.

Enzyme technology is an ever-growing field of knowledge and, in recent years, this technology has raised renewed interest, due to the search for new paradigms in several productive processes. Lipases, esterases and cutinases are enzymes used in a wide range of processes involving synthesis and hydrolysis reactions. The objective of this work was to investigate and compare the specific lipase and esterase activities of five enzymes - four already classified as lipases and one classified as cutinase - in the presence of natural and synthetic substrates. All tested enzymes presented both esterase and lipase specific activities. The highest specific esterase activity was observed for Aspergillus 1068 lipase in natural substrate and for F. oxysporum cutinase in synthetic substrate, while the highest specific lipase activity was observed for Geotrichum sp. lipase in natural substrate and for F. oxysporum cutinase in synthetic substrate. These results display some interface-independent lipolytic activity for all lipases tested. This is in accordance with the rationale that a new and broader definition of lipases may be necessary.
Lipases e esterases: como definir e classificar?
Keywords: lipase; esterase; cutinase; atividade específica de lipase; atividade específica de esterase; lipase; esterase; cutinase; lipase specific activity; esterase specific activity